Influence of ambient temperature on electrical properties of varistor-positor structure - Ivanchenko A. V.; Tonkoshkur A. S. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2022)
Recently, the combined two-layer structure based on varistor ceramics and polymer posistor nanocomposites with carbon filler (known as PolySwitch resettable fuses) has been seen as one of the promising elements for protecting electrical circuits from long-term overvoltages. The varistor and posistor layers are in thermal contact. The main functional property of such a structure is a sharp increase (by several orders of magnitude) in the electrical resistance of the posistor nanocomposite layer during the transfer of thermal energy from the varistor layer heated by overvoltage. Detailed information about the behavior of such combined varistor-posistor structures under different conditions, particularly in different temperature conditions, is necessary for the effective technical application of such structures as electrothermal overvoltage limiters. This paper offers research results on the effect of ambient temperature on the electrical characteristics of such voltage limiters. Structures based on metal oxide ceramics used in the production of serial varistors VCR 14D and a posistor nanocomposite for FRX-type PPTC fuses were used in the experiments of this study. It has been established that with an increase in the ambient temperature, the temperature and output voltage of such a device change insignificantly in the limitation region, while the current and power dissipation of the layers significantly decrease. At a fixed ambient temperature, the total power dissipated by the varistor and posistor layers practically does not change in the range of input voltage limitation. The dependence of the power dissipated by the varistor layer on the input voltage is identical to the analogous dependence of the current, and the power dissipation of the posistor layer tends to increase.